Assessing the Role of Islamic Jurisprudence in Climate Change Mitigation: Toward a Sharia-Informed Environmental Justice Framework - Achmad Murtadho; Agusniar Rizka Luthfia (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2024)
Climate change presents a significant global challenge that requires urgent and comprehensive action to mitigate its adverse effects on ecosystems, society, and the economy. Islamic jurisprudence, with its rich ethical framework, offers valuable insights into environmental justice, presenting a Sharia-informed approach to climate change mitigation. This study explores how principles of Sharia, such as Hifz al-Bi'ah (protection of the environment), Amanah (trust), and Isrāf (prohibition of wastefulness), can form a robust foundation for addressing environmental issues. Islamic law emphasizes the responsibility of humans as stewards of the Earth, encouraging sustainable resource management and the prevention of environmental degradation. The study further discusses how Sharia provides a proactive approach to environmental justice, focusing on prevention rather than simply reacting to environmental damage. Additionally, it explores how Islamic principles align with international environmental frameworks, offering a holistic approach to climate justice that respects both local traditions and global imperatives. The findings highlight the potential for integrating Sharia-based principles into contemporary environmental policies, particularly in Muslim-majority regions, where these values can enhance the legitimacy and effectiveness of climate change mitigation efforts. The paper concludes with recommendations for further research on the practical integration of Sharia principles into global climate policies and calls for collaboration among Islamic scholars, legal experts, and environmentalists to develop actionable, Sharia-based environmental policies that contribute to global climate action.